(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
One of the most important research areas in the field of Human -Computer-Interaction (HCI) is gesture recognition as it provides a natural and intuitive way to communicate between people and machines. Voice-based HCI applications range from computer applications to virtual/augmented reality and is recently being explored in other fields. This work proposes the implementation of absolute virtual mouse based on the interpretation of voice reorganization control. The procedure is to control the mouse pointer as for the mouse movement to up/down/left/right, open the file, dragging the file. This virtual device is designed specifically as an alternative non-contact pointer for people with mobility impairments in the upper extremities. The implementation of the virtual mouse by voice control is to make HCI simplification for disabled persons especially for the person who are not having the hands and arms, and Alternative mouse cursor positioning system for laptops.